A HISTORY OF APHORISMS IN ENGLISH LINGUISTICS (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
This article discusses aphorisms of the English languages and similarities and differences of aphorisms, sayings and proverbs. An aphorism is a comparatively wide term that summarizes the concepts of proverb, parable, interpretation, and wise saying that express the idea of wisdom. The main feature of the aphorisms is the brief artistic expression of a wise, typical thought, in which the expression, not the image, is the leader of meaning.